Analysis of Students’ Mathematical Problem-Solving Ability in Statistics Viewed from Sociomathematical Norms - Sumayyah Azzahro; Molli Wahyuni; Astuti Astuti (AL-ISHLAH: Jurnal Pendidikan, 2026)
The persistently low performance of Indonesian students in international assessments such as TIMSS and PISA indicates a critical gap in mathematical problem-solving skills. Beyond cognitive factors, sociomathematical norms—classroom-based standards for reasoning and discourse—may significantly influence how students approach and solve problems.This study employed a descriptive qualitative design. A sociomathematical norms questionnaire was administered to 27 tenth-grade students and categorized into high, medium, and low groups (Mean = 75.185; SD = 11.281). Six students (two from each group) were purposively selected for in-depth analysis. Data were collected through three statistical problem-solving tasks and clinical interviews. Students’ processes were analyzed using Polya’s four-stage framework: understanding the problem, devising a plan, carrying out the plan, and looking back.A strong positive relationship was found between sociomathematical norms and problem-solving proficiency. Students with high norms demonstrated mastery across all stages, including deep understanding, logical planning, systematic execution, and consistent reflective evaluation. Students with medium norms performed adequately in the first three stages for simpler problems but often omitted the “looking back” phase. Students with low norms exhibited fragmented understanding, ineffective planning, and difficulty executing and verifying solutions, often accompanied by low confidence.These findings highlight the importance of sociomathematical norms in fostering reflective and effective problem-solving practices.Strengthening sociomathematical norms can enhance students’ mathematical problem-solving abilities and support improved learning outcomes.